Network generation and analysis for the investigation of host-pathogen interactions in tuberculosis Holifidy Arisoa Rapanoel. - Rapanoel Holifidy Arisoa (Department of Molecular and Cell Biology, 2014)
Scroll down to electronic link to access the thesis.